2014
DOI: 10.1155/2014/874528
|View full text |Cite
|
Sign up to set email alerts
|

The Infrapopliteal Arterial Occlusions Similar to Buerger Disease: Report of Two Cases

Abstract: We herein present two cases that required the differential diagnosis of Buerger disease. Case 1 involved a 55-year-old male with a smoking habit who was admitted with ulcers and coldness in his fingers and toes. Angiography showed blockage in both the radial and posterior tibial arteries, which led to an initial diagnosis of Buerger disease. However, a biopsy of the right posterior tibial artery showed pathological findings of fibromuscular dysplasia (FMD). Case 2 involved a 28-year-old male with intermittent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…[26][27][28] In addition to the popliteal involvement, overall 25 FMD cases were reported through case reports or small case series involving iliac, femoral, tibial, and peroneal arteries in the lower extremity. [20,[29][30][31] In this report, the presented case (Case 1) is the first FMD case of popliteal artery obstruction in which nuclear PR positivity was demonstrated in myocytes and myofibroblasts of the hypertrophic segment. According to her medical history, the patient first experienced lower extremity vascular obstruction symptoms, when she was pregnant and she had a history of hormone intake for 20 years which are consistent with the studies suggesting the relationship between FMD and hormonal alterations.…”
Section: Discussionmentioning
confidence: 76%
“…[26][27][28] In addition to the popliteal involvement, overall 25 FMD cases were reported through case reports or small case series involving iliac, femoral, tibial, and peroneal arteries in the lower extremity. [20,[29][30][31] In this report, the presented case (Case 1) is the first FMD case of popliteal artery obstruction in which nuclear PR positivity was demonstrated in myocytes and myofibroblasts of the hypertrophic segment. According to her medical history, the patient first experienced lower extremity vascular obstruction symptoms, when she was pregnant and she had a history of hormone intake for 20 years which are consistent with the studies suggesting the relationship between FMD and hormonal alterations.…”
Section: Discussionmentioning
confidence: 76%
“…This pathology may sometimes be misdiagnosed as atherosclerosis or Buerger’s disease. Igari et al reported a case with PAES which had been misdiagnosed as Buerger’s disease [ 25 ]. There are of course cases of male smokers who present with complaints of bilateral intermittent claudication and are referred from orthopaedic clinics for suspicion of Buerger’s disease.…”
Section: Discussionmentioning
confidence: 99%